The Influence of Facilities and Infrastructure, Motivation, Compensation on the Performance of Public Elementary School Civil Servant Teachers in North Aceh Regency - Joko Wahyudi; Marwan Marwan; Saiful Bahri (Edumaspul: Jurnal Pendidikan, 2024)
Penelitian ini bertujuan untuk menganalisis Pengaruh Sarana dan Prasarana, Motivasi, Kompensasi Terhadap Kinerja Guru PNS Sekolah Dasar Negeri di Kabupaten Aceh Utara. Populasi dalam penelitian adalah keseluruhan guru PNS yang mengajar di SD Negeri di Kabupaten Aceh Utara khususnya di K3S Kutamakmur Kabupaten Aceh Utara sebanyak 29 sekolah dengan jumlah guru PNS sebanyak 225 orang. Dengan sampel sebanyak 144 orang. Teknik pengumpulan data dalam penelitian ini dengan cara penyebaran kuesioner atau angket. Pengolahan data dalam penelitian ini menggunakan SPSS for windows. Hasil penelitian menunjukkan bahwa sarana prasarana secara parsial mempunyai pengaruh positif signifikan terhadap kinerja guru PNS dengan nilai koefisien sebesar 0,277. Motivasi secara parsial mempunyai pengaruh positif signifikan terhadap kinerja guru PNS dengan nilai koefisien sebesar 0,277. Kompensasi secara parsial mempunyai pengaruh positif signifikan terhadap kinerja guru PNS dengan nilai koefisien sebesar 0,383. Sarana prasarana, motivasi, kompensasi secara simultan (bersama-sama) mempunyai pengaruh positif signifikan terhadap kinerja guru PNS Sekolah Dasar Negeri di Kabupaten Aceh Utara. Kata Kunci : Sarana prasarana, motivasi, kompensasi dan kinerja guru Abstract This research aims to analyze the influence of facilities and infrastructure, motivation, compensation on the performance of state elementary school civil servant teachers in North Aceh Regency. The population in the study were all civil servant teachers who taught in public elementary schools in North Aceh Regency, especially in K3S Kutamakmur, North Aceh Regency, 29 schools with a total of 225 civil servant teachers. With a sample of 144 people. The data collection technique in this research is by distributing questionnaires. Data processing in this research uses SPSS for Windows. The research results show that partial infrastructure has a significant positive influence on the performance of civil servant teachers with a coefficient value of 0.277. Motivation partially has a significant positive influence on the performance of civil servant teachers with a coefficient value of 0.277. Partial compensation has a significant positive influence on the performance of civil servant teachers with a coefficient value of 0.383. Infrastructure, motivation, compensation simultaneously (together) have a significant positive influence on the performance of state elementary school civil servant teachers in North Aceh Regency. Keywords: Infrastructure, motivation, compensation and teacher performance